Did foreign banks "cut and run" or stay committed to Emerging Europe during the crises? - John P. Bonin; Dana Louie (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
Our objective is to examine empirically the behavior of foreign banks regarding real loan growth during a financial crisis for a set of countries in which these banks dominate the banking sectors due primarily to having taken over large existing former state-owned banks. The eight countries are among the most developed in Emerging Europe, their banking sectors having been modernized by the beginning of the time period.We consider a data period that includes an initial credit boom (2004 – 2007) followed by the global financial crisis (2008 & 2009) and the onset of the Eurozone crisis (2010). Our main innovations with respect to the existing literature on banking during the financial crisis are to include explicit consideration of exchange rate dynamics and to separate foreign banks into two categories, namely, subsidiaries of the Big 6 European MNBs and all other foreign-controlled banks. Our results show that bank lending was impacted adversely by the crisis but that the two types of foreign banks behaved differently. The Big 6 banks remained committed to the region in that their lending behavior was not different from that of domestic banks corroborating the notion that these countries are a "second home market" for these banks. Contrariwise, the other foreign banks were primarily responsible for fueling the credit boom prior to the crisis but then "cut and ran" by decreasing their lending appreciably during the crisis. Our results also indicate different bank behavior in countries with flexible exchange rate regimes from those in the Eurozone. Hence, we conclude that both innovations matter in empirical work on bank behavior during a crisis in the region and may, by extension, be relevant to other small countries in which banking sectors are dominated by foreign financial institutions.
URN:NBN:fi:bof-201511231445
Keywords: P34; G01; G15; 330